Algorithm of the flying device's power plant of the same type automatic design - Синеглазов, B. M.; Брикалов, А. В. (Proceedings of National Aviation University (archive), 2021)
Algorithm of solution of multicriterial task of solid propellant power plant optimum designing, based on the LP search method, is considered. The criteria are formulated, variable parameters and restrictions are defined.